The passage of time - Noonan, Harold W. (De Gruyter, 2015)
Eric Olson argues that the dynamic view of time must be false. It requires that the question ‘How fast does time pass?’ has an answer. But its only possible answer, one second per second, is not an answer. I argue that Olson has failed to identify what is wrong with talk of time’s passage. Then I argue that, nonetheless, he is right to reject it. To say that time passes is analogous to saying that space is dense, and to ask about the rate of time’s passage is analogous to asking how dense space is. Since the questions are on a par the dynamic view of time, which requires that they are not, is mistaken.